Infants who develop eczema at 12 months have a deficient T regulatory cell response to microbial stimuli at the time of birth - Ismail, Intan Hakimah (Elsevier, 2012)
Rationale T Regulatory (Treg) cells and may play an essential role in regulating early immune development and shaping the immune response toward a proallergic or tolerant status. Proinflammatory cytokines may be associated with tolerance induction.